2020
DOI: 10.1164/rccm.202001-0180oc
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Acid Ceramidase Reduces Inflammation and Infection in Cystic Fibrosis

Abstract: Rationale: In cystic fibrosis the major cause of morbidity and mortality is lung disease characterized by inflammation and infection. The influence of sphingolipid metabolism is poorly understood with a lack of studies using human airway model systems. Objectives: To investigate sphingolipid metabolism in cystic fibrosis and the effects of treatment with recombinant human acid ceramidase on inflammation and infection. Methods: Sphingolipids were measured using mass spectrometry in fully differentiated cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 57 publications
1
40
1
Order By: Relevance
“…www.nature.com/scientificreports/ group is in line with the reference range of circulating sphingolipid in human plasma from healthy subjects 41 , our study suffers of limited numerosity of included patients, which can partially explain this discrepancy. Moreover study design and blood sampling modality (different anticoagulants) may influence LC-MS/MS results 41,42 . Notably, the increase of different ceramide species has been shown to concur to the upregulation of different acute phase proteins, and to leucocytes recruitment and activation [43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…www.nature.com/scientificreports/ group is in line with the reference range of circulating sphingolipid in human plasma from healthy subjects 41 , our study suffers of limited numerosity of included patients, which can partially explain this discrepancy. Moreover study design and blood sampling modality (different anticoagulants) may influence LC-MS/MS results 41,42 . Notably, the increase of different ceramide species has been shown to concur to the upregulation of different acute phase proteins, and to leucocytes recruitment and activation [43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the concentration sphingolipid species in control group is in line with the reference range of circulating sphingolipid in human plasma from healthy subjects 41 , our study suffers of limited numerosity of included patients, which can partially explain this discrepancy. Moreover study design and blood sampling modality (different anticoagulants) may influence LC–MS/MS results 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to sphingosine, studies from several laboratories have demonstrated that ceramide levels are higher in CF epithelial cells than in normal cells (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The imbalance between ceramide and sphingosine in the respiratory tract was shown to be mediated by a down-regulation of the acid ceramidase protein expression correlating with a marked reduction of the activity of the acid ceramidase in tracheal and bronchial epithelial cells of mice and humans (9,19).…”
Section: Staphylococcus Epidermidismentioning
confidence: 99%
“…We and others have recently reported that the lipid composition of CF airway epithelial cells is significantly altered with an increase of ceramide and a decrease of sphingosine in the luminal membrane of tracheal and bronchial epithelial cells (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%